O-042 ESHRE good practice recommendations on chromosomal mosaicism. (30th June 2022) - De Rycke, M; Capalbo, A; Coonen, E; Coticchio, G; Fiorentino, F; Goossens, V; MCheik, S; Rubio, C; Sermon, K; Sfontouris, I; Spits, C; Vermeesch, J; et al.
Abstract: The implementation of high-resolution genome-wide methods, usually next-generation sequencing-based, in preimplantation genetic testing (PGT), has led to the frequent detection of embryos with chromosomal mosaicism (whole chromosome and/or segmental aberrations). Despite a growing series of papers showing the birth of healthy babies following the transfer of embryos indicating mosaicism on PGT-A analysis - albeit with lower implantation rates and higher miscarriage rates in comparison with euploid embryo transfer - many questions remain, making it difficult to decide on how to handle chromosomally mosaic embryos in the clinic. A dedicated ESHRE working group developed good practice recommendations on how to manage chromosomal mosaicism in clinical practice. The recommendations were formulated based on the expert opinion of the working group while taking into consideration the published data and outcomes of a survey on current practices in 239 PGT laboratories and ART clinics, mostly within Europe, Asia and America. The recommendations with regards to detection and management of chromosomal mosaicism were developed following the manual for development of ESHRE good practice recommendations with a stakeholder review of the paper on the ESHRE website. In addition to the recommendations, the working group identified missing information and scientific questions, which should guide further research in PGT, with relevance to the occurrence, detection and impact of chromosomal mosaicism. Trial registration number: